Social Skills and Their Relationship to Mental Health Among Female Leaders in the Scout Movement - Eman Mohamed Al-Hamali (Journal of Scientific and Human Dimensions, 2026)
The current study aimed to uncover the impact of social skills on mental health. The study sample consisted of 33 female leaders from the Benghazi Girl Guides and Boy Scouts Commission, randomly selected from various guiding ranks. The study utilized Ronald Riggio's Social Skills Inventory (SSI), translated by Ibrahim Al-Samadoni (1991), and the Mental Health Scale developed by Kamel Al-Zubaidi and Sanaa Al-Hazza (1997).The study yielded several results, including:•              Social Skills Levels: There were no statistically significant differences between the sample's arithmetic mean and the scale's hypothetical mean. This indicates that the level of social skills among the female leaders at the Benghazi Scout and Guide Commission falls within the theoretically expected level and does not fundamentally differ from it.•              Mental Health Levels: The results showed that the sample members enjoy a level of mental health that statistically exceeds the theoretical mean of the scale.•              Correlation: A positive correlation was found between social skills and mental health among the leaders. The results revealed a direct relationship with a moderate correlation strength between the two variables, meaning that as the leaders' social skills level increases, their mental health level rises, and vice versa.Although the correlation coefficient value is not high, it reflects a statistically significant correlation, confirming that social skills are one of the factors associated with mental health, without being the sole influencing factor. Based on these findings, the researcher presented a set of recommendations and proposals that open new horizons for future research.
Keywords: Social skills; mental health; female leaders; the scouting movement